Applying drone technologies and robotics for agricultural sustainability - Chelliah, Pethuru Raj ca. 20./21. Jahrhundert; Saini, Kavita 1976-; Feitosa Pacheco, Vinicius (IGI Global, 2023)
As digital intelligence and transformation technologies continue to emerge and evolve, this book is attempts to demystify how the pioneering digital technologies impact the agricultural field deeply and decisively.
Keywords: Aeronautics in agriculture; Sustainable agriculture; Micro air vehicles -- Industrial applications; Aufsatzsammlung